Policy of criminalization under Islamic criminal justice system: a new paradigm of analysis - Olagunju-Ibrahim, Ridwan Olawale; Olodo Al-Shafi’i, Mohammed Muneer’deen; Md Sidek, Suzana Suhailawaty; Mohamed El Khayat, Mostafa Hassan (International Publications, 2025)
The rationale in Islamic law behind criminalization of some unbecoming acts has some distinguishing features which are basically meant to showcase the distinctive comprehensiveness and super eminence of the law of Allahu swt over all other legal systems – be they man-made, spiritual or celestial. Islamic penal system as an integral part of Islamic law is faith-based. The relationship between a Muslim and his creator is a very strong one, and so is his conviction in the religion of Allahu swt and in Islamic law. It is this strong bond of man with Allahu swt that compels the impressive rate of man’s compliance with the dictates of Shari’ah often times. This solid bond of communion enables the Islamic criminal law to be effective in taming the tide of crime spread and achieving maximum good of the society. The positive effect of the divine law in this regard is stronger, more pronounced and better felt when compared to other legal paradigms across the globe. The man-made laws are found to be lacking in this divinity-inspired awe and diffidence from the public who are expected to obey the so- called laws with dispatch. As a result, neglect and indifference to the commandments designed by man to shape and regulate the world become a usual occurrence and thus horrible crimes of different forms and volumes continue to spread around on daily basis. In addition to the foregoing on the effectiveness of Islamic law in tackling the menace of crime, mention must be made of the deep-rooted principle of Islam that there shall be no punishment/sanction except there is criminalization, and there can never be criminalization except through a given text. Quite unlike the practice in the man-made law of crime, this principle is under the divine law given a so wide and elastic compass of interpretation that no perpetrator of unbecoming act will escape punishment upon trial and establishment of guilt. The writers follow a doctrinal method of consulting relevant primary and secondary materials of shari’ah to analyze the special salient features of this law which have made combating crimes possible. Upon employing this literary method, the need finding is that combating crimes is not only possible, but also easier, faster and less expensive to engage in.